Optimizing antipsychotic dosing for relapse prevention in cannabis-induced psychosis: A nationwide cohort study - Mustonen, Antti; Niemelä, Solja; Denissoff, Alexander; Di Forti, Marta; Tanskanen, Antti; Mittendorfer-Rutz, Ellenor; Tiihonen, Jari; Taipale, Heidi (Elsevier, 2026)
Background
Cannabis-induced psychosis (CIP) carries a high risk of relapse. Research has shown that antipsychotic medications are effective in relapse prevention after first diagnosed CIP. Given that antipsychotics carry the potential for dose-related adverse effects, understanding the optimal dose is critical. Therefore, we conducted a dose–response analysis to evaluate the real-world effectiveness of oral antipsychotics in preventing relapse after CIP.
Methods
We used data from linkage of administrative and health care registers from Sweden to identify all individuals with first diagnosis of CIP (ICD-10 F12.5). We modelled oral antipsychotic exposure (aripiprazole, clozapine, risperidone, olanzapine, quetiapine, antipsychotic polytherapy, other oral antipsychotics) as time-dependent using validated PRE2DUP-method. Dose–response association of antipsychotic exposure and outcome were examined across three predefined daily dose (DDD) categories (<0.6, 0.6–<1.4, ≥1.4) using within-individual models in a stratified Cox-regression analysis. The primary outcome was hospitalization for any psychotic episode, defined as schizophrenia-spectrum disorder (F20–F29) or substance-induced psychosis (F1x.5) as the main diagnosis.
Results
We identified 1,772 individuals aged 16-64 years with first-time CIP between 2006 and 2021. Antipsychotic polytherapy was associated with reduced risk of psychosis hospitalization across all dose ranges (HRs=0.54–0.65). Clozapine (0.6–<1.4 DDDs/day), olanzapine (≥0.6 DDDs/day), aripiprazole (0.6–<1.4 DDDs/day), risperidone (<0.6 DDDs/day), and other oral antipsychotics (0.6–<1.4 DDDs/day) were effective, while quetiapine showed no significant benefit.
Conclusions
Findings indicate dose-dependent real-world effectiveness of antipsychotics in CIP, with most agents performing best at 0.6–<1.4 DDDs/day. These results support optimizing dosing of oral antipsychotic medications for relapse prevention after CIP to balance efficacy and adverse effects.